Design and Deployment of Secured Cloud Assist IIoT - SCADA System for Real Time Parameter Monitoring and Control in Process Control Applications - D. Deivasigamani; R. Vinoth Kumar (Technological Innovation in Engineering Research Vol. 4, 2022)
In this work, we have developed secured SCADA based real time process parameter monitoring and control using Industrial IoT(IIoT) with Cloud Assist feature. Nowadays IIoT is being used by hundreds of process plants in thousands of unique applications globally. The parameters in process industries like Level, Flow, Temperature and Pressure are being monitored and controlled using cloud storage also presented. Cloud refers for accessing computer information over internet. We have used ‘ThingSpeak’ IoT analytics platform to aggregate, visualize and analyze all real time data of a process during run time, and it can be implemented with LabVIEW platform for more flexibility. Flow, temperature, pressure, and level may all be monitored and controlled wirelessly in this system using wireless sensors that communicate in full duplex mode. Passkey allows secure access to cloud data. In the event that any malfunctions occur, an alarm system is employed to notify the end user. The process station contains a wireless transmitter that sends data periodically, and the receiving portion has a Wi-Fi module that receives sent data. All of them are saved on the Cloud, which allows remote devices such as PCs, mobile phones, and tablets to access and control the data wirelessly. Furthermore, it may be coupled with automation tools such as SCADA and PLC with bidirectional control to assure operational safety and efficiency using the most up-to-date automation protocols.